Forming of professional and pedagogical competence of a future teacher of technologies in the modular training system - Кучер, Зоя (Pedagogy of Higher and Secondary Education, 2014)
Kucher Z. S. Forming of professional and pedagogical competence of a future teacher of technologies in the modular training system. The article deals with the concept “professional and pedagogical competence”. Principles of making professionally oriented modular programs and conditions of their implementing in technological education are defined. The special attention is given to continuity of studying the special disciplines like sewing and using project technologies.